Household structure and its association with sexual risk behaviours and sexual health outcomes: evidence from a British probability sample survey. Issue 12 (4th December 2018) - Curtis, Tyrone J; Field, Nigel; Clifton, Soazig; Mercer, Catherine H
Abstract : Objectives: Economic and social changes over the last 20 years have led to changes in the living situations of young people in Britain. A person's home-life context might influence their sexual behaviour, with implications for their sexual healthcare needs; we investigated this hypothesis. Methods: Britain's third National Survey of Sexual Attitudes and Lifestyles, a probability sample survey undertaken in 2010–2012, interviewed 15 162 men and women aged 16–74 years in Britain (with 3869 aged 16–24 years). We examined household structure by gender and age group. We then focused on sexually experienced young people (aged 16–24 years), and used multivariable models to explore associations between household structure, sexual risk behaviours and sexual health outcomes, independent of confounders including age, relationship status, employment and area of residence. Results: Young people were most likely to be living with parents (women 57.1% (95% CI 54.5% to 59.6%) and men 68.7% (95% CI 65.4% to 71.8%)) or non-relatives (women 10.5% (95% CI 8.5% to 12.9%) and men 12.6% (95% CI 10.1% to 15.6%)). Among the 81.3% of young people who were sexually experienced, compared with young women living with parents (reference category), young women living alone or with non-relatives had a higher likelihood of reporting ≥2 sexual partners (adjusted OR 1.54 (95% CI 1.03 to 2.31); 1.76 (95% CI 1.03 to 3.00), respectively). Women living alone were also more likely to have had unsafe sex (2.04 (95% CI 1.38 to 3.02)). Despite these differences in sexually transmitted infection (STI) risk, there was no difference in sexual healthcare-seeking behaviour. Young men and women living with partners reported lower levels of sexual risk behaviours. Conclusions: Our study suggests household structure may influence the sexual behaviour of young people in Britain. Given changes in their living arrangements, the role of household structure in sexual health research should be further investigated, and also considered as a possible marker for STI risk in clinical consultations.